Effect of Early Weightbearing Following Open Reduction and Internal Fixation of Unstable Ankle Fractures on Wound Complications or Failures of Fixation. (December 2019) - Pyle, Casey; Kim-Orden, Michael; Hughes, Tyler; Schneiderman, Brian; Kay, Robert; Harris, Thomas
Background: There is a growing trend toward early weightbearing as tolerated (WBAT) after open reduction and internal fixation (ORIF) of ankle fractures. To date, studies have excluded fractures with associated syndesmotic injuries from their cohorts. Methods: In this retrospective cohort study, a chart review was performed at a single level 1 trauma center, identifying all unstable ankle fractures that underwent operative fixation between July 2016 and July 2017. After exclusion criteria, 63 patients were identified and 31 were included in the final analysis, with 14 undergoing syndesmotic fixation. WBAT was initiated after suture removal, between 2 and 4 weeks postoperatively. Outcomes included fracture union, radiographic maintenance of alignment, hardware failures, wound complications, and the need for repeat surgery. Results: Weightbearing was initiated at an average of 17.8 days. All 31 patients progressed toward fracture union, with no hardware failures. Three patients developed superficial wound breakdown, which was treated with protected weightbearing in all cases and oral antibiotics in 1 case. All 3 went on to heal from their incisions. One patient had delayed wound breakdown and required a split-thickness skin graft that subsequently healed without complication. One patient underwent hardware removal 6 months postoperatively. There were no revision ORIF procedures. Conclusion: There is literature supporting early WBAT after ORIF of unstable ankle fractures in patients without major comorbidities. This article supports this trend, demonstrating that a group of ankle fractures requiring syndesmotic fixation were included in the early weightbearing cohort without a higher rate of catastrophic failure or increased wound problems. Level of Evidence: Level IV, retrospective cohort study.